GE Transportation: A Case Study of the Potential to Improve Performance. Issue 2 (21st February 2013) - Wertz, R. James
Abstract This case study uses Thomas Gilbert's second leisurely theorem as a theoretical framework to evaluate the potential to improve performance at GE Transportation, a small but important sector of General Electric. The author concludes that GE Transportation's potential to improve performance of 1.044 will be difficult for the company to maintain during its ongoing global expansion as a result of emergent labor‐ and infrastructure‐related issues.